PENGARUH KOMPOSISI TANAMAN TERHADAP IKLIM MIKRO PADA RUANG TERBUKA HIJAU KAMPUS A UNIVERSITAS TRISAKTI - Qurrotu ‘Aini Besila; Ina Krisantia; Diana Irvindiaty Hendrawan (Jurnal Lingkungan dan Kota, 2022)
Campus A of Trisakti University is located in Kyai Tapa Street, Grogol, West Jakarta. The campus area is diminutive with remaining green open spaces (GOS) that composed by various vegetation, especially in the plaza area- the main outdoor place in the campus. This research aims to identify vegetation types and compositions, and to discern its effect on the microclimate of GOS in Trisakti University. The research used descriptive quantitative method with purposive sampling in several places: Campus A plaza, roof garden in the 9th floor of building K, and open space in Grogol Terminal. The latter place was used as a comparison between the campus area and the non-campus area. Vegetation composition analysis was conducted to know the relation between vegetation composition and microclimate. Besides temperature and relative humidity, the comfort level was also measured by using the Temperature Humidity Index (THI). The result shows that the biodiversity in the roof garden is higher than the plaza area. However, the canopy coverage in the plaza is better than the roof garden. So that the average temperature in the plaza is lower than the roof garden and Grogol Terminal- which only has few trees. The temperature in the plaza is 27,5-28.8 oC, while the roof garden and Grogol Terminal temperature are ranging around 27.7-30.0 oC and 29.3-31.9 oC respectively. Furthermore, the relative humidity in the plaza is higher than the roof garden and Grogol Terminal. Relative humidity in the plaza is 74.1%-78.3%, roof garden is 80.1%-82.8%, and Grogol Terminal is 69.7-77.1%. Therefore, it can be inferred that the plaza has a better comfort level than the roof garden and Grogol Terminal. The result also shows that there is a relation between vegetation composition and microclimate. A composition which has more stratification and various plant habitus tends to create a better microclimate, which can increase the users’ comfort.